Outdoor performance evaluation of a novel photovoltaic heat sinks to enhance power conversion efficiency and temperature uniformity - Ibrahim, Adnan (Elsevier Ltd, 2022)
The non-uniformity of photovoltaic (PV) temperature can further deteriorate its power conversion efficiency and technical lifetime over long field exposures. This study proposed novel fins for a PV module temperature reduction and enhancing temperature uniformity. The proposed multi-level fin heat sinks (MLFHS) consist of a novel geometry of extruded aluminum material attached to the rear side of the PV module. The developed outdoor experimental setup consists of two identical 120 Wp monocrystalline PV modules; one served as a reference module for comparison against the module with the proposed novel heat sink geometry. The temperature distributions across PV modules and the electrical parameters were then recorded and analysed. A substantial drop in the module temperature of 8.45 ◦C was observed at solar irradiance and ambient temperature of 941 W/m2 and 36.17 ◦C, respectively. As a result, the heat sink improved the overall power output up to 9.56% under outdoor operating conditions. Furthermore, the prominent effect of temperature uniformity was perceived for solar irradiance greater than 600 W/m2 and improved by 14.8%. These findings are foundational for passive cooling methodologies to guide further research and development of an efficient PV cooling methodology.